Implementation of agile methodologies and model-based systems engineering for the management, design and development of a low earth orbit cubesat mission (2024)
ABSTRACT : This work presents a case study on the integration of Agile Systems Engineering methodologies in the preliminary design phase of satellite systems, focusing on the 3ColStar satellite mission. Through Model Based Systems Engineering (MBSE), technical consistency was rigorously managed across various architectural models, ensuring coherency, and minimizing errors. Furthermore, with the implementation of the Arcadia Method, supported by the Capella modelling tool, the preliminary design was developed, and the use of digital engineering tools such as GMAT, Maltab/Simulink and python for validation and verification allowed the digitalization of the system represented in models that contain requirements, architecture, and the interfaces between the parts of the system. At the same time, the preliminary design process was streamlined and completed within an accelerated timeframe of 4 months, with weekly sprints driving progress based on the scrum methodology. This case study highlights the effectiveness of Agile Systems Engineering principles in enhancing the accuracy, communication, and efficiency of satellite systems preliminary design, providing valuable insights for future missions.Moreover, an adapted scrum framework is designed and proposed for the management of the following phases of the project.